Creating the hybridoma to produce monoclonal antibodies causing the agglutination of the human red blood cells containing A antigen - Trung, Nguyễn Thị; Hằng, Nguyễn Thị; Hằng, Vũ Thị Thu; Phan, Lê Văn; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2016)
The determination of ABO blood group is obliged in many cases especially before blood transfusion, that is indicated at Point a, Clause 4, Article 14 Circular 26/2013/TT-BYT - Vietnam, date 09.16.2013. For this purpose, both standard sera (monoclonal antibodies) and standard red blood cells are common used but monoclonal antibodies are prefered. In Vietnam, monoclonal antibodies against ABO blood group are not available in domestic production. In this study, we succeeded in the generation of hybidoma cells secreting anti-A monoclonal antibody. Firstly, Balb/c mice were injected with Vietnamese human group A red blood cells to evoke B lymphocyte cells against A antigen present on the surface of the red blood cells. Afterward the lymphocytes were fused with sp2/0 myeloma cells in the presence of polyethylene glycol (PEG) to gain hybrid cells that were identified through ability to expand cells in a selective medium (hypoxanthine aminopterine thymine - HAT) at 37°C and 5% CO2. During screening and isolation process, the positive clones were identified by agglutination test with standard group A red blood cells. Of the 1440 wells, 12 monoclonal hybrid clones were selected. The hybrid cell line (designated A6G11C9) was the best one secreting the highest anti-A monoclonal antibody into culture with the antibody titer of 512. The antibody showed good intensity (+++), and the agglutination was visible by 10 seconds. This antibody is the promising for ABO-grouping kit development